Different proxies, different stories? Imperfect correlations and different determinants of fitness in bighorn sheep. Issue 12 (8th December 2022) - Van de Walle, Joanie; Larue, Benjamin; Pigeon, Gabriel; Pelletier, Fanie
Abstract: Measuring individual fitness empirically is required to assess selective pressures and predicts evolutionary changes in nature. There is, however, little consensus on how fitness should be empirically estimated. As fitness proxies vary in their underlying assumptions, their relative sensitivity to individual, environmental, and demographic factors may also vary. Here, using a long‐term study, we aimed at identifying the determinants of individual fitness in bighorn sheep ( Ovis canadensis ) using seven fitness proxies. Specifically, we compared four‐lifetime fitness proxies: lifetime breeding success, lifetime reproductive success, individual growth rate, individual contribution to population growth, and three multi‐generational proxies: number of granddaughters, individual descendance in the next generation, and relative genetic contribution to the next generation. We found that all proxies were positively correlated, but the magnitude of the correlations varied substantially. Longevity was the main determinant of most fitness proxies. Individual fitness calculated over more than one generation was also affected by population density and growth rate. Because they are affected by contrasting factors, our study suggests that different fitness proxies should not be used interchangeably as they may convey different information about selective pressures and lead to divergent evolutionary predictions. Uncovering the mechanisms underlying variation in individual fitness and improving our ability to predict evolutionary change might require the use of several, rather than one, the proxy of individual fitness. Abstract : Fitness is central to ecology and evolution, but it is typically proxied using several contrasting approaches, which can lead to contrasting conclusions about fitness determinants and selection. Using seven proxies of individual fitness in bighorn sheep, we showed that fitness proxies were positively correlated, but the magnitude of the correlations varied substantially. We also showed that depending on the fitness proxy, fitness determinants and predictions about selection varied, suggesting that fitness proxies should not be used interchangeably.